Incomplete Cor Triatriatum Dexter and Its Clinical and Technical Implications in Interatrial Shunt Device‐Based Closure: An Intracardiac Echocardiography Study. (17th February 2016) - Rigatelli, Gianluca; Dell'Avvocata, Fabio; Giordan, Massimo; Vassilev, Dobrin; Cardaioli, Paolo
Abstract: Objectives: Cor triatriatum dexter (CTD) is a congenital anomaly in which the right atrium is divided into two parts by a membrane or fibromuscular band. Incomplete separation of the right atrium may occur when prominent venous valve remnants such as Eustachian valve (EV) or Chiari network (CN) incompletely divided the right atrium (incomplete CTD‐iCTD). We sought to assess the incidence of EV/CN and iCTD and its clinical and technical implications in patients submitted to interatrial shunt transcatheter closure. Design: Retrospective analysis of single center registry. Setting: Secondary referral center. Patients: Five hundred eighty consecutive patients (mean age 44 ± 15.5 years, 385 females) who had been submitted over a 12 years period to intracardiac echocardiography‐aided interatrial shunt catheter‐based closure. Outcomes Measures: Prevalence of iCTD and EV/CN, shunt grade, right ventricle diameter, incidence of intraprocedural complications. Results: In patients with PFO, a prominent EV or a large CN and iCTD have been diagnosed in was diagnosed on ICE in 51.1% and 5.2%, respectively. In ASD patients, a prominent EV or a large CN and iCTD were apparent in 13.7% and 5.6%, respectively. PFO patients with iCTD had more frequently a curtain pattern on TC Doppler and a larger right‐to‐left shunt graded than prominent EV/CN patients and patients without. ASD patients with iCTD had larger right ventricle diameter than both ASD patients with EV/CN and patients without. iCTD was associated with 45.1% of patients with intraoperative complications. Conclusions: iCTD are not so infrequently observed by ICE during interatrial shunt closure procedure. Presence of this peculiar structure should be taken in account during device‐based procedure in the right atrium.